2008
DOI: 10.1111/j.1479-8298.2008.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of pselaphine beetles (Coleoptera: Staphylinidae: Pselaphinae) in eastern Thailand

Abstract: Pselaphine beetles (Coleoptera: Staphylinidae: Pselaphinae) are cosmopolitan, species-rich, and yet poorly studied, particularly in the tropics. We sampled beetles in three types of primary forest and two types of disturbed forest habitats in eastern Thailand to assess the utility of pselaphine beetles as bioindicators of forest disturbance. We simultaneously measured leaf litter mass, soil moisture, soil acidity and canopy cover at each site to infer which environmental factors affect pselaphine beetle divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…This key finding of the present study of higher species richness in less disturbed lowland deciduous forests from Laos agrees with other studies of the subject. For instance, Sakchoowong et al (2008) found that teak plantations and secondary forest had substantially fewer individuals and species of pselaphine beetles in a study conducted in eastern Thailand. Another study showed that abundance, species richness and guild structure of saproxylic beetles were not maintained in a logged and regrowth forest in Queensland, Australia (Grove 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This key finding of the present study of higher species richness in less disturbed lowland deciduous forests from Laos agrees with other studies of the subject. For instance, Sakchoowong et al (2008) found that teak plantations and secondary forest had substantially fewer individuals and species of pselaphine beetles in a study conducted in eastern Thailand. Another study showed that abundance, species richness and guild structure of saproxylic beetles were not maintained in a logged and regrowth forest in Queensland, Australia (Grove 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A Winkler extraction method was used to sample leaf litter macrofauna (see Krell et al, for a discussion on this method). The Pselaphinae beetles (Coleoptera: Staphylinidae: Pselaphinae) inhabit forest leaf litter (Nomura & Mohamed, ; Sakchoowong et al, ), therefore Winkler sampling is appropriate. Sieved leaf litter samples were hung in Winkler bags for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…The Pselaphines are a species‐rich group of predatory leaf litter beetles with 9,854 described living species in 1,247 genera worldwide (Parker, ). They are generally small (∼1–3 mm in body length) and are particularly diverse and abundant in the tropics (Chandler, ; Chung et al, ; Parker & Maruyama, ; Nomura & Mohamed, ; Sakchoowong et al, ). In Borneo, 123 species have been recorded (Nomura & Mohamed, ), but many more are yet to be described.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations